MANAJEMEN PEMBELAJARAN DI MI I’ANATUL MUTA’ALLIMIN 01 KUBANGWUNGU KETANGGUNGAN BREBES - Dina Salamah; Fathul Fauzi (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
Education quality improvement programs in Indonesia are still experiencing various problems ,one of which is the learning process that is less effective and many teachers still do not understand how to learn effectively. That’s why we need good learning management.This study aims to describe the learning management of MI I’anatul Muta’allimin 01 Kubangwungu. This research method is qualitative descriptive. The result of study show that (1) the planning of learning is made in the form syllabus, the semester planning, learning implementation plan, semester program, annual program, learning methods, and learning media to be used, (2) the organizing of learning the teacher determines the method of learning that is in accordance with the material to be taught,(3) the implementation of learning at MI I’anatul Muta’allimin 01 Kubangwungu begins with introductions, core activities, and closing, and (4) supervision/evaluating in this learning teacher conducts test aimed at knowing the ability and learning outcomes of student during the learning process as well as teachers conduct some assessment of the student’s personality. The conclusion of this study is the implementation of learning management at MI I’anatul Muta’allimin 01 Kubangwungu is in accordance with the criteria and prosedures that have been set before. Keywords: Management, Learning, Education References Danawarti, Yanti Sri. 2013. Manajemen Pembelajaran Dalam Upaya Meningkatkan Mutu Pendidikan .Jurnal Mimbar Bumi Bengawan. 6 (13). Alfian Erwinsyah. 2017. Manajemen Pembelajaran Dalam Kaitannya Dengan Peningkatan Kualitas Guru, Jurnal Manajemen Pendidikan Islam. 5 (1). Manullang, Martua. 2014. Manajemen Pembelajaran Matematika. Jurnal Pendidikan dan Pembelajaran. 21 (2). Rayuni, Dewi. 2010. Manajemen Pembelajaran di Madrasah Aliyah Negeri (MAN) 3 Palembang. Jurnal Pendidikan Islam, 15 (1).